IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN IPS DI MADRASAH TSANAWIYAH MUHAMMADIYAH SRUMBUNG KABUPATEN MAGELANG - Suryaningsih, Putri; Salam, Rudi (SOSIOLIUM : Jurnal Pembelajaran IPS, 2020)
MTs Muhammadiyah Srumbung is a school with strong Islamic teachings. Character education is delivered through two stages, namely the classroom culture and the culture of the school environment. This article aims to 1) Know the implementation of character education in social studies learning, 2) Know the students' responses to the implementation of character education in social studies learning, 3) Know the inhibiting and supporting factors for the implementation of character education in social studies learning. The results of the study found that 1) Implementation of character education in social studies learning through classroom culture and school environment. Class culture goes through the planning, learning and evaluation process, while school culture is through habituation and extracurricular activities in schools, 2) The response of students to the implementation of character education is positive, 3) The inhibiting and supporting factors are school (teachers and students), parents and the environment. MTs Muhammadiyah Srumbung is a school with strong Islamic teachings. Character education is delivered through two stages, namely the classroom culture and the culture of the school environment. This article aims to 1) Know the implementation of character education in social studies learning, 2) Know the students' responses to the implementation of character education in social studies learning, 3) Know the inhibiting and supporting factors for the implementation of character education in social studies learning. The results of the study found that 1) Implementation of character education in social studies learning through classroom culture and school environment. Class culture goes through the planning, learning and evaluation process, while school culture is through habituation and extracurricular activities in schools, 2) The response of students to the implementation of character education is positive, 3) The inhibiting and supporting factors are school (teachers and students ), parents and the environment.